Design, synthesis and antibacterial activities against Xanthomonas oryzae pv. oryzae, Xanthomonas axonopodis pv. Citri and Ralstonia solanacearum of novel myricetin derivatives containing sulfonamide moiety. Issue 3 (5th September 2019) - Jiang, Shichun; Tang, Xu; Chen, Mei; He, Jun; Su, Shijun; Liu, Liwei; He, Ming; Xue, Wei
Abstract: BACKGROUND: Myricetin and sulfonamide derivatives exhibited a wide variety of biological activity. In order to develop highly bioactive molecules, novel myricetin derivatives containing sulfonamide moiety were synthesized and antibacterial activities were investigated. RESULTS: The results of bioassays indicated that compound A12, having an EC50 value of 4.7 μg mL −1, exhibited the best in vitro antibacterial activities against Xanthomonas oryzae pv. oryzae ( X. oryzae pv. o .); EC50 values for this compound were even better than those of thiodiazole‐copper (TC, 71.4 μg mL −1 ) and bismerthiazol (BT, 54.7 μg mL −1 ). Compound A2, having an EC50 value of 1.1 μg mL −1, exhibited the best in vitro antibacterial activities against Xanthomonas axonopodis pv. citri ( X. axonopodis pv. c ); values were notably better than those of TC (60.0 μg mL −1 ) and BT (48.9 μg mL −1 ). Scanning electron microscopy analysis indicated that compounds A2 and A12 caused the cell membranes of X. axonopodis pv. c and X. oryzae pv. o . to break or deform, respectively. When the concentration of compound A12 was 100 μg mL −1, the effective curative activity against bacterial leaf blight of rice was 44.2% in vivo and the effective protection activity was 58.2% in vivo, results that were both better than values for TC (18.9 and 21.4%, respectively) and BT (12.5 and 12.5%, respectively). CONCLUSION: Novel myricetin derivatives containing a sulfonamide moiety were synthesized and bioassay results showed that compounds A2 and A12 exhibited the best antibacterial activities. © 2019 Society of Chemical Industry Abstract : Novel myricetin derivatives containing sulfonamide moiety were synthesized. Compounds A2 and A12 exhibited the best antibacterial activities against X. axonopodis pv. c and X. oryzae pv. o ., respectively.